A four-act play. Philosophy and science: the impact on management theory and practice - Wickhorst, Vickie, author; Geroy, Gary D., advisor (Colorado State University. Libraries, 2005)
Science, philosophy, and management theory share common roots. The earliest philosophers were the scientists of their day, engaging their peers via discourse and written form. Metaphysics was not separate of science it was science; philosophers discussed human existence and the nature of Being based on reason and observation of the world around them. Plato, for example, theorized on both the meaning and the basis of life. The question this document is concerned with is whether a study of the interaction between science, philosophy, and written communication can provide insight into the changes wrought in daily life, both in the community and within organizations. The answer to this will enable us to look at emerging science and philosophy today so that we can better understand the possible future we may be dealing with in organizational settings. The research question is: What relationship and possible timeline can we discover between philosophy, science, and literature that can help us understand the forces that impact management theory within organizations? The method used for this study, although accepted within the field of qualitative research, is relatively new. This study will employ a qualitative research methodology referred to as philosophical hermeneutics and the research will be conveyed in the format of a performance text. Quite literally, the reader will engage with the topic via a four-act play in which the narrator will guide the reader through history and into the present day, interacting with characters who have been affected by western philosophy, science, and literature, and who are part of life within various organizations.
Keywords: philosophy; science history; theater; exegesis and hermeneutics; studies; Judaism